Successful Neurological Recovery with Multimodality Therapy without Surgery for Spinal Metastases from Advanced Gastric Cancer - Hideyuki Kinoshita; Hiroto Kamoda; Takeshi Ishii; Yoko Hagiwara; Toshinori Tsukanishi; Yusuke Amanuma; Rino Nankinzan; Sumihisa Orita; Kazuhide Inage; Naoya Hirosawa; Seiji Ohtori; Tsukasa Yonemoto (Case Reports in Orthopedics)
Advanced gastric cancer with bone metastasis has a very poor prognosis with short median survival. To the best of our knowledge, no reports in literature have described extensive recovery of paralysis with multimodality treatment without surgery in these cases. This report describes the case of a 52-year-old severely paralyzed female patient with spinal metastasis from advanced gastric cancer. She was inoperable, owing to a large thrombus in the inferior vena cava; alternative multimodality treatments, including chemotherapy and radiotherapy, were administered. The paralysis and the bladder and rectal dysfunction improved considerably. In addition, the performance status (PS) and Frankel grade also improved dramatically, from 4 to 1 and grade B to D, respectively. At 1 year after initiation of treatment, she is ambulatory. Patients with poor PS are often offered palliative therapy. However, this case demonstrates that poor PS solely due to paralysis from spinal metastasis may necessitate multimodality treatment instead of palliative care.